Perceptions on the importance of note reading for brass band training amongst band instructors / Mohamad Zulkarnain Tahmir - Tahmir, Mohamad Zulkarnain (Faculty of Music, 2017)
There are things need to know from students before entering the band and before they learn to recognize the instruments. This is very important for teachers to know and understand their students to the knowledge that they know and do not know. The purpose of this study was to examine the instructors' perceptions on the importance of note reading for beginner students before entering band. Surveys given to instructors in Malaysia, Indonesia, Thailand, and Philippines. There are 19 participants in this study. I examine instructors the musical characteristics, such as singing, improvising, composing, chanting, and reading notation, to know the importance of teaching for new students before entering the band. In this study, participants identified and ranked concepts and skill are important for students.